Chicken soup for the soul our 101 best stories: on being a parent; inspirational, humorous, and heartwarming stories about parenthood - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy. (Cos Cob, CT CSS, 2008)
A collection of 101 of the best stories and poems from Chicken Soup's library, written by parents about the experience of being a parent - the joys, the sorrows, the fun times, amusing anecdotes, and helpful advice in the form of personal stories. Oriented towards parents of all ages with children of all ages.
Keywords: Parenthood -- Literary collections; Parenthood -- Anecdotes; Parents -- Literary collections; Parents -- Anecdotes